The Implementation of School Literacy Movement: A Literature Review - Herry Augustinus Simarmata; Siti Drivoka Sulistyaningrum (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of the study is to describe a literature review on the implementation of the School Literacy Movement throughout the country. The article searches were conducted using databases: Google Scholar, Science Direct, and Springer, and the keywords 'School Literacy Movement' and 'Gerakan Literasi Sekolah'. The authors establish inclusion criteria and exclusion criteria and obtained 8 relevant articles. The study was conducted in 5 stages: article collection, article reduction, display, discussion, and conclusions. The implementation of the School Literacy Movement in Indonesian schools follows the theories used as references. The School Literacy Movement is being implemented successfully, and it has the potential to increase student literacy while also meeting one of the government programs outlined in the 2013 National Curriculum.